Strategi Dinas Komunikasi dan Informatika dalam Mendukung Smart City Melalui Aplikasi Wargaku di Kota Surabaya - Rofpi, Ahmat; Tukiman (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
Surabaya city is one of the cities in Indonesia that has implemented the concept of a smart city and has been awarded as the leading city in the main category of Smart City Rating. Based on the Duties and Functions of the Surabaya City Department of Communication and Informatics in 2021, the department introduced an application known as